PENGARUH GREEN ACCOUNTING, GREEN INTELLECTUAL CAPITAL, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN - Roza, Putri; Ruhiyat, Endang (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the impact of green accounting, green intellectual capital, and corporate social responsibility on company performance. The research was conducted by analyzing sustainability reports and financial statements of companies in the mining sector (minerals) listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The sample used in this study consists of 12 mining companies (minerals) listed on the Indonesia Stock Exchange during the period from 2019 to 2023, using random sampling technique. The data used in this study is secondary data in the form of sustainability reports and financial statements from each company included in the sample. The variables used in this study are Green Accounting (X1) as the first independent variable, Green Intellectual Capital (X2) as the second independent variable, and Corporate Social Responsibility (X3) as the third independent variable, while Company Performance (Y) serves as the dependent variable. The panel data regression method is used as the research methodology in this study. The analysis of the research results is conducted using EViews 13 software. The findings indicate that the best model is the Fixed Effect Model (FEM). The results show that green accounting, green intellectual capital, and corporate social responsibility have a significant impact on company performance. Specifically, corporate social responsibility has a significant and positive effect on company performance, while green accounting and green intellectual capital do not have a significant impact on company performance. Keywords: Green Accounting, Green Intellectual Capital, Corporate Social Responsibility, Company Performance.